Allergic contact dermatitis: From pathophysiology to development of new preventive strategies. (December 2020) - Brites, Gonçalo Sousa; Ferreira, Isabel; Sebastião, Ana Isabel; Silva, Ana; Carrascal, Mylene; Neves, Bruno Miguel; Cruz, Maria T.
Graphical abstract: Abstract: As the body's first line of defense, the skin is the organ most frequently exposed to chemicals present in personal hygiene products, household products, or materials used in the work environment. In this context, skin disorders account for more than 40 % of all occupational and work-related diseases, constituting a significant public health burden. Among skin disorders, allergic contact dermatitis (ACD) is the most prevalent occupational disease and the most common form of immunotoxicity in humans. ACD is a T-cell-mediated skin inflammation resulting from the priming and expansion of allergen-specific CD4 + and CD8 + T cells. The clinical condition is characterized by local skin rash, itchiness, redness, swelling, and lesions, being mainly diagnosed by the patch test. Upon ACD diagnosis, avoiding the exposure to the triggering allergen is the mainstay of treatment to prevent future flares. In cases where avoidance is not possible, the use of a standard of care interim treatments such as steroid creams or ointments, barrier creams, and moisturizers are strongly recommended to alleviate symptoms. In this review, we sought to provide the reader with an overview of the pathophysiology of ACD as well as the currently available pharmacological treatment options. Furthermore, a comprehensive outline of several preventive strategies is also provided.